Development of Geospatial Framework for Crop Water Stress and Drought Monitoring Using Remote Sensing and GIS for Sangamner Taluka, Maharashtra, India - Ganesh Sadashiv Dighe; Onkar Tukaram Gadge; Nikita Sanjay Deshmukh; Sayali Arun Ghule; Mayuri R. Gadhe (Universitas Gadjah Mada, 2026)
Agricultural drought in semi-arid India threatens food security, particularly during the Rabi season when crops rely on limited irrigation. This study presents an integrated geospatial framework for village-scale crop water stress and drought monitoring, demonstrated in Sangamner Taluka, Maharashtra. The framework combines Landsat 8/9 thermal and multispectral imagery with ERA5-Land soil moisture, CHIRPS rainfall, and MODIS evapotranspiration. An empirical Crop Water Stress Index (ES-CWSI) is computed using NDVI-derived emissivity and scene-specific percentile normalization of land surface temperature, enabling spatially relative stress assessment. A composite Drought Severity Index (DSI) conditionally integrates ES-CWSI, root-zone soil moisture, and rainfall deficits. Processing occurs across three layers: Google Earth Engine for quality-controlled data acquisition, QGIS and Python for index computation, and a web dashboard for visualization and internal validation. Analysis of the 2025–2026 Rabi season reveals substantial intra-taluka variability, with 58.9% of villages experiencing persistent high stress and peak stress occurring on 13 March 2026 (mean ES-CWSI = 0.579). Strong correlations between ES-CWSI and NDVI (? = −0.81), soil moisture (? = −0.68), and DSI (? = 0.96) confirm physical consistency. The framework provides an operationally robust, uncertainty-aware system suitable for regional agricultural advisory applications.